Kebebasan Beragama Dalam Konstitusi Dan Perspektif Hak Asasi Manusia - Susilo, Bernardinus Doni Sulistyo (Belom Bahadat, 2024)
Religion is a guide or guidance for its followers. Embracing a religion is a human right of all individuals which has been guaranteed and protected by the state through the constitution. The purpose of writing this article is to reveal transparently based on the rules or constitution the freedom to embrace a religion. The method used in this research is normative law. Where data obtained through legal materials and legal articles is analyzed systematically. The result is that freedom of religion based on the constitution is contained in the values ​​of Pancasila as the ideology of the nation and state, especially the first principle. The 1945 Constitution in article 28 D (1) also explains freedom of religion and this is a guideline for every religious community in embracing and practicing their beliefs. Likewise, based on human rights law number 39 of 1999 and also the Universal Declaration of Human Rights (UDHR) it is clear that it states the protection and freedom to embrace a religion. The conclusion is that embracing a religion must be based on one's own wishes and beliefs, it is not permissible for other people or certain parties to intervene in this matter because it is a human right. In carrying out religious life, there must be no discrimination, no matter how small. This is because religious freedom is regulated by the constitution, so it is obligatory to obey the law.